PENGARUH PEMBELAJARAN MELALUI LUMIO BY SMART TERHADAP MATHEMATICAL RETTENTION SISWA PADA MATERI LINGKARAN - Syaifur Rohman; Maimunah; Tri Susilaningtyas (Jurnal Penalaran dan Riset Matematika, 2024)
This research seeks to explore the impact of learning using the Lumio by smart platform on students' mathematics retention in circle material in class VIII SMP 01 Islam Jember. The research employed an experimental method with a quasi-experimental design. Posttest only control group. The research sample consisted of two classes, each consisting of 20 students. One class designated as the experimental group using learning via Lumio by smart, while the other class was utilized as a control group using conventional learning. The instrument employed is a test to measure the level of student retention of circle material. The research findings indicated a decrease in scores from pretest to posttest in the control class (51.00 to 48.2), while the experimental class experienced an increase from pretest to posttest (50.00 to 65.75). Analysis using the Wilcoxon test showed significance (0.00 < 0.05).